2021
DOI: 10.3390/jcm10071424
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Biomarkers of Pain in Saliva and PAINAD Scale in Elderly People with Cognitive Impairment and Inability to Communicate

Abstract: The pain assessment in advanced dementia (PAINAD) appears to be a clinically useful tool. However, the salivary determination of tumor necrosis factor receptor type II (sTNF-RII) and secretory IgA (sIgA) as pain biomarkers is still incipient. The aim was to correlate the PAINAD score with sTNF-RII and sIgA biomarker levels in the saliva of patients with advanced dementia. In this regard, a cross-sectional study was conducted. The sample consisted of 75 elderly patients with a clinical diagnosis of dementia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Another study found higher d-serine levels in the serum and cerebrospinal fluid (CSF) of persons suffering from AD [41]. Antczak and colleagues [42] showed that transcranial magnetic stimulation (TMS) had some possibilities for improving the diagnostic accuracy and treatment of dementia, whereas the salivary immunological markers-sTNF-RII and sIgA-might be possible pain markers in dementia [43]. Another study showed that a dual-task test might be a helpful tool in differentiating patients with depression, MCI, and dementia [44].…”
Section: Other Immune-related Markersmentioning
confidence: 99%
“…Another study found higher d-serine levels in the serum and cerebrospinal fluid (CSF) of persons suffering from AD [41]. Antczak and colleagues [42] showed that transcranial magnetic stimulation (TMS) had some possibilities for improving the diagnostic accuracy and treatment of dementia, whereas the salivary immunological markers-sTNF-RII and sIgA-might be possible pain markers in dementia [43]. Another study showed that a dual-task test might be a helpful tool in differentiating patients with depression, MCI, and dementia [44].…”
Section: Other Immune-related Markersmentioning
confidence: 99%
“…Thirteen studies were performed in a hospital setting [ 16 , 18 29 ], 33 in care home facilities [ 17 , 30 61 ] and two studies were based in both care home and people’s home settings [ 62 , 63 ]. Two studies were performed both in care home and hospital settings [ 64 , 65 ]. The location of study was not stated in Lorenzet et al [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies assessed the PAINAD [ 16 , 20 24 , 40 , 44 47 , 65 ]. Overall, the level of evidence for the PAINAD tool was limited (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] Both soluble tumour necrosis factor-α receptor II (sTNF-RII) and sIgA can be a reliable salivary biomarkers for pain assessment but sTNF-RII can be more accurate in diagnosing pain in people with advanced dementia. [ 14 ] Alpha-amylase and IgA were present in higher amounts in the saliva of a patient with burning mouth syndrome [ 15 ] and these markers could be used as pain biomarkers. [ 16 ] The studies regarding pain assessment using salivary biomarkers are limited.…”
Section: Discussionmentioning
confidence: 99%